SYSTEMATIC LITERATURE REVIEW: EFFECT OF CORRELATED COLOR TEMPERATURE (CCT) ON PIANISTS' RESPONSES (Jurnal Arsitektur ARCADE, 2026)
The quality of piano performance, both in music education and recitals, is often disrupted by psychological pressure and cognitive load that affect concentration. External factors, particularly interior design elements such as stage or studio lighting, are known to affect pianist physiological and cognitive conditions non-visually. This study aims to integrate empirical findings regarding the impact of Correlated Color Temperature (CCT)—specifically comparing warm (3000K) and cool (6000K) color temperatures—on pianists' responses using the Systematic Literature Review (SLR) method. Literature evaluation was conducted using the PRISMA guidelines, with a synthesis of findings categorized into three main aspects: lighting, musical performance, and the validity of physiological indicators. Relational density analysis of these aspects indicates a significant research gap in previous studies: heart rate measurement proved to be less sensitive in assessing the effects of CCT on cognition. Conversely, Electroencephalography (EEG) is highly valid for measuring emotional responses and brain connectivity during piano playing, but this instrument has not been specifically applied to test lighting variables. These findings highlight the need for neurodesign integration using EEG instruments to validate the impact of 3000K and 6000K CCTs on pianists' responses. This can also serve as a foundation for evidence-based design practices in performance spaces and music schools.